Time to recovery from visceral leishmaniasis and its predictors of mature visceral leishmaniasis patients admitted at Metema Hospital, Metema, Ethiopia - Habitamu Wudu; Chekol Alemu (Scientific Reports)
Abstract Visceral leishmaniasis (VL) is a neglected tropical disease that mostly affects the working-class and impoverished segments of society, having a significant negative effect on the economic development of the affected nation. While anti-leishmanial medications lower mortality among VL patients, patients may still die or require more time to recover (TTR) while receiving treatment. In this regard, there are limited studies in Ethiopia. This study aims to determine the time to recovery and its associated predictors among adult VL patients at Metema Hospital. A hospital-based cross-sectional study design was employed, and the data were collected in patient’s charts from September 2017 to September 2021. Data were entered and analyzed using Epi-data, STATA version 14.2, and R 3.4.0 statistical software. The Kaplan–Meier survival curve and log-rank tests were used to compare the survival time. The Cox proportional hazard model assumption and model fitness were checked and used to identify statistical association predictors in VL patients. The Cox proportional hazard (Cox-PH) model was fitted. The overall medium recovery time was 7 days (minimum 4, maximum 14 days). The variables nasal bleeding (adjusted hazard ratio/AHR: 0.44; 95% CI: 0.19–0.89), no comorbidity (AHR: 2.29; 95% CI: 1.27–4.11), relapse VL (AHR: 0.33; 95% CI: 0.15–0.75),low parasite load (AHR: 2.58; 95% CI: 1.48–4.51), and ambulatory (AHR: 3.26; 95% CI: 2.45–6.53) were significantly associated with TTR in VL patients. Patients with comorbidities, nasal bleeding, relapse VL, bedridden, and high parasite load should be treated and monitored carefully to recover quickly from their illness.